2016
DOI: 10.1002/bies.201600060
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts over host manipulation between different parasites and pathogens: Investigating the ecological and medical consequences

Abstract: When parasites have different interests in regard to how their host should behave this can result in a conflict over host manipulation, i.e. parasite induced changes in host behaviour that enhance parasite fitness. Such a conflict can result in the alteration, or even complete suppression, of one parasite's host manipulation. Many parasites, and probably also symbionts and commensals, have the ability to manipulate the behaviour of their host. Non‐manipulating parasites should also have an interest in host beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 107 publications
(200 reference statements)
2
15
0
2
Order By: Relevance
“…By contrast, host manipulation changed within a few generation in a similar experiment in which only the parasite was under selection (Hafer-Hahmann, 2019). It fits well, however, with previous speculations that rather than actually resisting host manipulation, hosts could alter their baseline behavior to counter and accommodate host manipulation by a very prevalent and co-evolved parasite, but resulting in a suboptimal phenotype in the absence of this parasite (Hafer, 2016;Read & Braithwaite, 2012;Weinersmith & Earley, 2016). In infected copepods, this altered level of activity was decreased by not yet infective parasites and increased by infective parasites.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…By contrast, host manipulation changed within a few generation in a similar experiment in which only the parasite was under selection (Hafer-Hahmann, 2019). It fits well, however, with previous speculations that rather than actually resisting host manipulation, hosts could alter their baseline behavior to counter and accommodate host manipulation by a very prevalent and co-evolved parasite, but resulting in a suboptimal phenotype in the absence of this parasite (Hafer, 2016;Read & Braithwaite, 2012;Weinersmith & Earley, 2016). In infected copepods, this altered level of activity was decreased by not yet infective parasites and increased by infective parasites.…”
Section: Discussionsupporting
confidence: 80%
“…In order to avoid being attacked by the perceived predator, copepods should reduce their activity following this "attack" (Benesh, 2010a;Hafer & Benesh, 2015;Hafer & Milinski, 2015, 2016Hammerschmidt et al, 2009). In order to avoid being attacked by the perceived predator, copepods should reduce their activity following this "attack" (Benesh, 2010a;Hafer & Benesh, 2015;Hafer & Milinski, 2015, 2016Hammerschmidt et al, 2009).…”
Section: Behavioral Recordings and Additional Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both allo-grooming and secretion of antibiotic compounds are two often cited examples reported in social insects 1 4 . Conversely, some pathogens have been reported to alter host behavior to favor their own transmission and enhance their replication and virulence 5 . Studies of non-social insects have reported reduced feeding (anorexia) and changes in dietary macronutrient preference in pathogen-challenged individuals, both of which are associated with an enhanced ability to cope with pathogen infections likely via starvation of resident pathogens from essential macronutrients or trade-offs in energy allocation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it is more difficult to assess how benefits and costs are traded off against each other. Costs entails energetic effort of the parasite, final host resistance to manipulation (Mazzi & Bakker, 2003; see previous section), intermediate host mortality (Mazzi & Bakker, 2003), conflict over manipulation when infected with different parasite stages of the same species or different parasite species with contrasting interests (Hafer, 2016;Hafer & Milinski, 2015, or transmission to dead-end hosts (e.g., Poulin et al, 2005). Milinski (1990) distinguishes two ways in which parasites can influence host's decision-making.…”
Section: Future Directionsmentioning
confidence: 99%